Investigation of stress distribution in multi-layered targets under impact load by using receding contact method. (15th November 2020) - Tan, Mengting; Zhang, Xianfeng; Bao, Kuo; Chen, Beibei
Abstract: As a fundamental nature in controlling the failure mechanism of a multi-layered target under impact, the stress distribution of each layer in target should be solved. A theoretical model of stress distribution of multi-layered target with finite thicknesses under impact load is established by using receding contact theory. Numerical calculations of targets with different configurations are carried out to figure out how the stress distribution dominates the failure pattern. The numerical results of stress distribution and the formation of cone crack in semi-infinite ceramic of current model agree well with Hertz's contact theory and the experiment from literature, respectively. The effect of target configuration on the failure of ceramic–metal target is predicted and discussed in terms of the same areal density target. The results show that the crack extends and changes its path with the increasing thickness ratio of ceramic and metal, meanwhile, the yield area in metal decreases laterally. The mechanical properties of metal affect both the crack path in ceramic and the yield degree in metal, while the mechanical properties of ceramic affect more the yield area in metal.